Running-specific prostheses reduce lower-limb muscle activity compared to daily-use prostheses in people with unilateral transtibial amputations - Sepp, L. A.; Nelson-Wong, E.; Baum, B. S.; Silverman, A. K. (Journal of Electromyography and Kinesiology, 2020)
People with unilateral transtibial amputation (TTA) have biomechanical differences between the amputated and intact legs and compared to people without TTA during running. Additional biomechanical differences emerge between running with running-specific (RSPs) and daily-use prostheses (DUPs), but the associated underlying muscle activity is unclear. We collected surface electromyography from the biceps femoris long head, rectus femoris, vastus lateralis, and gastrocnemius as well as body kinematics and ground reaction forces in six people with and six people without TTA. We compared stance phase muscle activity and peak activation timing in people with and without TTA and between people using RSPs compared to DUPs during running at 3.5 m/s. Peak amputated leg hamstring activity occurred 34% (RSP) and 31% (DUP) earlier in stance phase compared to the intact leg. Peak amputated leg rectus femoris activity of people wearing DUPs occurred 8% and 9% later in stance phase than the intact leg of people wearing DUPs and amputated leg of people wearing RSPs, respectively. People with TTA had 45% (DUP) and 61% (RSP) smaller peak amputated leg knee extension moments compared to people without TTA, consistent with observations of quadriceps muscle activity. Using RSPs decreased overall muscle activity compared to DUPs.